REVOLUSI MENTAL DALAM MENERAPKAN SISTEM EKONOMI ISLAM - Sappeami Sappeami (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2018)
This paper examines the mental revolution in applying the Islamic economics system which is expected to open the horizon of humans’ thought, especially Muslims, so as they are always careful in carrying out all economics activities. The significance embodied in the idea of the mental revolution is the transformation of the ethos, namely the fundamental change in the mentality, the way of thinking, the way of feeling, and the way of believing that is proven in daily behavior and actions. The mistake which occurs in the economics system of this modern era vastly needs a mental revolution to restore the consciousness of economics actors that the world is only an intermediary towards the real life in hereafter so that the economics activities will constantly be performed with good and correct actions dealing with Al-Qur’an and As-Sunnah.